Single cell RNA-sequencing profiling to improve the translation between human IBD and in vivo models - Karmele, Erik P.; Moldoveanu, Ana Laura; Kaymak, Irem; Jugder, Bat-Erdene; Ursin, Rebecca L.; Bednar, Kyle J.; Corridoni, Daniele; Ort, Tatiana (Frontiers in Immunology, 2023)
Inflammatory bowel disease (IBD) is an umbrella term for two conditions (Crohn’s Disease and Ulcerative Colitis) that is characterized by chronic inflammation of the gastrointestinal tract. The use of pre-clinical animal models has been invaluable for the understanding of potential disease mechanisms. However, despite promising results of numerous therapeutics in mouse colitis models, many of these therapies did not show clinical benefits in patients with IBD. Single cell RNA-sequencing (scRNA-seq) has recently revolutionized our understanding of complex interactions between the immune system, stroma, and epithelial cells by mapping novel cell subpopulations and their remodeling during disease. This technology has not been widely applied to pre-clinical models of IBD. ScRNA-seq profiling of murine models may provide an opportunity to increase the transability into the clinic, and to choose the most appropriate model to test hypotheses and novel therapeutics. In this review, we have summarized some of the key findings at the single cell transcriptomic level in IBD, how specific signatures have been functionally validated in vivo, and highlighted the similarities and differences between scRNA-seq findings in human IBD and experimental mouse models. In each section of this review, we highlight the importance for utilizing this technology to find the most suitable or translational models of IBD based on the cellular therapeutic target.